2023
DOI: 10.3350/cmh.2023.0057
|View full text |Cite
|
Sign up to set email alerts
|

Treated chronic hepatitis B is a good prognostic factor of diffuse large B-cell lymphoma

Abstract: Background/Aims: Chronic hepatitis B (CHB) is a risk factor for non-Hodgkin lymphoma (NHL). Our recent study suggested that antiviral treatment may reduce the incidence of NHL in CHB patients. This study compared the prognoses of hepatitis B virus (HBV)-associated diffuse large B-cell lymphoma (DLBCL) patients receiving antiviral treatment and HBV-unassociated DLBCL patients.Methods: This study comprised 928 DLBCL patients who were treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Lemaitre et al [ 2 ] found that when DLBCL is treated with R-CHOP and antivirals, patients (n=24) with HBV infection have similar outcomes to the non-HBV-infected patients. In addition, the median age of the patients with HBV-NHL was 59 years [ 2 ], which is close to that shown by Park et al [ 1 ] (56 years). These two studies suggest that treating HBV might be beneficial for most patients with DLBCL, whether they are in prevalent or non-prevalent areas.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Lemaitre et al [ 2 ] found that when DLBCL is treated with R-CHOP and antivirals, patients (n=24) with HBV infection have similar outcomes to the non-HBV-infected patients. In addition, the median age of the patients with HBV-NHL was 59 years [ 2 ], which is close to that shown by Park et al [ 1 ] (56 years). These two studies suggest that treating HBV might be beneficial for most patients with DLBCL, whether they are in prevalent or non-prevalent areas.…”
supporting
confidence: 78%
“…In conclusion, we appreciate the valuable work by Park et al [ 1 ], which provided new insight into the treatment of patients with HBV-associated DLBCL. If it is possible to broaden the scope to include wider age ranges and non-endemic areas, we can gain a more comprehensive understanding of the treatment’s efficacy and ensure that it caters to a wider population.…”
mentioning
confidence: 87%
See 2 more Smart Citations